A concise review on hypophosphatasia with case report - Kaur, Jaspinder; Nourabadi, Soheila; Chavez, Luis; Sachemchi, Issac (International Journal of Medicine, 2016)
Hypophosphatasia (HPP) is an inherited dento-osseous metabolic disease characterized by inactivating mutations in the gene encoding the tissue-nonspecific isoenzyme of alkaline phosphatase (TNSALP) which lead to a deficiency in TNSALP enzymatic activity. Low TNSALP activity results in increased levels of 3 known phosphocompound substrates: inorganic pyrophosphate (PPi), pyridoxal 5’-phosphate (PLP; the major circulating form of vitamin B6), and phosphoethanolamine (PEA). We discussed a systematic review with novel approach and a case report in which patient had multiple jaw reconstructive surgeries and early tooth loss in his childhood age but remained undiagnosed till his 60s. It should raise awareness among health care providers regarding low TNSALP and performing thorough etiological investigations which can ensure optimal clinical care and decision making for their patients by preventing complications like chondrocalcinosis, arthritis, early tooth loss, pseudo/complete fractures and pseudogout among the patients diagnosed with HPP even later in their life.